Impact of axial root growth angles on nitrogen acquisition in maize depends on environmental conditions - Dathe, A. (Ann Bot, 2016)
Backgrounds and Aims Crops with reduced requirement for nitrogen (N) fertilizer would have substantial benefits in developed nations, while improving food security in developing nations. This study employs the functional structural plant model SimRoot to test the hypothesis that variation in the growth angles of axial roots of maize (Zea mays L.) is an important determinant of N capture. Methods Six phenotypes contrasting in axial root growth angles were modelled for 42 d at seven soil nitrate levels from 10 to 250 kg ha(−1) in a sand and a silt loam, and five precipitation regimes ranging from 0·5× to 1·5× of an ambient rainfall pattern. Model results were compared with soil N measurements of field sites with silt loam and loamy sand textures. Key Results For optimal nitrate uptake, root foraging must coincide with nitrate availability in the soil profile, which depends on soil type and precipitation regime. The benefit of specific root architectures for efficient N uptake increases with decreasing soil N content, while the effect of soil type increases with increasing soil N level. Extreme root architectures are beneficial under extreme environmental conditions. Extremely shallow root systems perform well under reduced precipitation, but perform poorly with ambient and greater precipitation. Dimorphic phenotypes with normal or shallow seminal and very steep nodal roots performed well in all scenarios, and consistently outperformed the steep phenotypes. Nitrate uptake increased under reduced leaching conditions in the silt loam and with low precipitation. Conclusions Results support the hypothesis that root growth angles are primary determinants of N acquisition in maize. With decreasing soil N status, optimal angles resulted in 15–50 % greater N acquisition over 42 d. Optimal root phenotypes for N capture varied with soil and precipitation regimes, suggesting that genetic selection for root phenotypes could be tailored to specific environments.